Algunas consideraciones sobre la responsabilidad del empleador ante daños causados al trabajador - Ágreda Aliaga, Jorge Orlando (2019)
Liability as a civil concept against contractual and non-contractual damages has been a widely discussed subject by civil doctrine, but underdeveloped from Peruvian labour law.In this paper the author provides an outline of the fi eld considering legal literature and the rules applicable in the relationship between the worker and the employer, with an emphasis in the critic of judicial rulings that are ineffi cient and create legal uncertainty.